Audit Fee Determinants: The Influence of Corporate Governance Mechanisms in Nigerian Banking Industry - Ifunanya, Nwosu Lilian; Ogundele, Omobolade Stephen; Mahlaule, Calvin (International Review of Management and Marketing, 2025)
This study examined the influence of corporate governance on audit fees of the Deposit Money Banks (DMBs) in Nigeria by exploring secondary data. The study population comprised 13 DMBs in Nigeria, of which 12 were purposively selected based on data availability. Data were sourced from the annual reports and accounts of 12 listed DMBs in Nigeria spanning from 2012 to 2023. This study explored multiple regression analysis by using dependent variables (Audit Fees), independent variables (Board Meetings, Board Size, Board Independence, Board female Gender Diversity, CEO Ownership & Female Audit Committee), and control variables (Return on Asset, Firm Size, Asset Growth & Leverage). The findings indicated that Board female Gender Diversity, Female Audit Committee, Firm Size & Asset Growth had positive and significant effects on audit fees, while (Return on Asset & Leverage) had negative and significant effect on audit fees. The result concluded that corporate governance influences the audit fees of DBMs in Nigeria. Given the financial scandals and regulatory reform that is prevalent in the Nigerian banking sector. This study contributes to the literature by providing empirical evidence on how corporate governance affects audit fees within the Nigerian banking sector, reinforcing the need for effective governance policies.